Chronic SSRI stimulation of astrocytic 5-HT2B receptors change multiple gene expressions/editings and metabolism of glutamate, glucose and glycogen: a potential paradigm shift - Hertz, Leif; Rothman, Douglas L.; Li, Baoman; Peng, Liang (Frontiers in Behavioral Neuroscience, 2015)
It is firmly believed that the mechanism of action of SSRIs in major depression is to inhibit the serotonin transporter, SERT, and increase extracellular concentration of serotonin. However, this undisputed observation does not prove that SERT inhibition is the mechanism, let alone the only mechanism, by which SSRI’s exert their therapeutic effects. It has recently been demonstrated that 5-HT2B receptor stimulation is needed for the antidepressant effect of fluoxetine in vivo. The ability of all 5 currently used SSRIs to stimulate the 5-HT2B receptor equipotentially incultured astrocyteshas been known for several years,and increasing evidence has shown the importance of astrocytes and astrocyte-neuronal interactions for neuroplasticity and complex brain activity. This paper reviews acute and chronic effects of 5-HT2B receptor stimulation in cultured astrocytes and in astrocytes freshly isolated from brains of mice treated with fluoxetine for 14 daystogether with effects ofanti-depressant therapy on turnover of glutamate and GABA and metabolism of glucose and glycogen. It is suggested that these events are causally related to the mechanism of action of SSRIs and of interest for development of newer antidepressant drugs.